Adsorption of textile reactive dyestuffs by treatment sludges of inorganic nature - Tünay, Olcay; Metin, Emine; Olmez-Hanci, Tuğba; Kabdaşli, Işik (Informa UK Limited, 2012)
Colour removal from industrial effluents, particularly from the textile industry, has become an important requirement as the adverse effects ofdyestuffs, such as toxicity, on the environment have been proven. Adsorption is a commonly used treatment method for colour removal. Although activated carbon is very effective for this purpose, a number of natural materials and waste materials, such as waste sludges generated from treatment systems, have been tested to reduce the cost of the process. In this paper, sludges arising from the operation of an electrocoagulation process that used stainless steel or aluminium electrodes were investigated as adsorbents for decolorization of reactive dyestuffs. Electrocoagulation waste sludges produced with the use of stainless steel electrodes provided higher than 90% or complete decolorization of Crimson HEXL, Yellow HE4R and RB5 dyestuffs. The sludge produced with aluminium electrodes yielded colour adsorption between 95% and 100% at a 1 g/L dose and pH 8.5-9.1 for two of the dyestuffs; the removal of RB5 did not exceed 60% up to a 4.76 g/L dose. FeCl3 coagulation and adsorption using freshly precipitated coagulation sludge resulted in poor colour removals of 10% for all three dyestuffs. The superior colour adsorption performance of electrocoagulation waste sludges was attributed to modification of the surface properties of the sludges during the electrocoagulation operation. A batch-wise kinetic study indicated that the adsorption of RB5 on to electrocoagulation waste sludges was well fitted by the pseudo-second-order kinetic model, suggesting the intra-particle diffusion process as the rate-limiting step of the adsorption process.
Keywords: Sewage; Textile Industry; Electrocoagulation; Industrial Waste; Adsorption; Coloring Agents; Electrodes; Waste Disposal, Fluid; Aluminum